ANALISIS SOAL LATIHAN PADA BUKU PAKET MATEMATIKA SMA YANG BERSESUAIAN DENGAN HIGHER ORDER THINKING SKILL - Yenusi, Tersia; Mumu, Jeinne; Tanujaya, Benidiktus (Universitas Papua, 2019)
The purpose of this research to analyze exercise question on Mathematics textbook of senior high school which associated with higher order thinking skills (HOTS). HOTS according to Taxonomy Bloom can be classified into aspect: analysis (C4), evaluate (C5), and Create (C4). This is a qualitative study using the method of evaluation in education field. The object of this research is exercise questions on mathematics textbook of senior high school used in SMA YPK Oikumene, Manokwari, West Papua. The instrument used to categorize the exercise question is operational verbs (KKO). Data were analyzed using descriptive data analysis. Furthermore, the result shows that 3.90% question can be categorized as analysis domain, 0.65% questions reach evaluate domain, and there is no question can be group as create domain.